A literature review on the technologies of bonded hoses for marine applications - Amaechi, C.V. (Taylor and Francis Ltd., 2022)
Marine bonded hoses are conduit-tubular structures used for loading, discharging, transferring and transporting fluid products like oil, gas, and water. These marine conduits are applied in the offshore industry by utilising novel marine materials and sustainable technologies. Based on sustainability, there are advances made as solutions for challenging environments. These challenges include scouring gases, deep water regions, changing sea water temperatures, platform loads and vessel motions. These environments also require sustainable materials like marine composites. This paper reviews historical timeline and patent development of hoses in the marine environment. It highlights key developments on marine hoses and their configurations. These configurations include FPSO-FSO with hose attachments in catenary configurations and CALM buoy-PLEM in Lazy-S configurations. The review also discusses the evolutions in the hose designs, potentials of the hoses, and recent state-of-the-art developments in the industry. Comprehensive discussions with necessary recommendations are made for fluid applications in the offshore industry. Â© 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.